Μελέτη καθυστερήσεων σε κατασκευαστικά έργα της Κύπρου - Οδυσσέως, Μαρία (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The appearance of the delays is a major problem that affects negatively the construction projects of the country. Throughout this survey there will be a further analysis of the subject being with the use of a questionnaire in which a determination of the mist common causes of the delay regarding the construction projects in Cyprus. Also, the actions that the participants made for addressing these delays, as well as the degree of which the economical crisis affected the management of the projects and their consequences regarding the delays. Also, how the use of the software assisted for scheduling the projects. With the creation of working program a solution or escape can be found, or if its application is useful for managing these projects. Specifically, the research was conducted in 50 engineers, mainly from the Private Sector, and a small number of them came from the Public Sector. Moreover, the data were analysed through Microsoft Excel and conclusions, solutions and comments were derived. There is also reference based on the terms of the contracts, regarding to when the can demand and claim extension of time. Finally, there is an explanation of the Analysis Methods used to identify the delays As Planned, versus those used As Built, those used as Planned Impacted and As Built But For, through the MS Project Program. Subsequently, a conclusion was derived to which was the best method for analysis and monitoring the project. Lastly, a reference is also made for the compensations and demands that are attributable according to the type of the delays.
Keywords: Constructions projects delays; Cyprus; Causes of the delay; Projects management; Scheduling the projects; Analysis methods; Καθυστερήσεις κατασκευαστικών έργων; Κύπρος; Αίτια καθυστερήσεων; Διαχείρηση έργων; Εργολάβος; Μέθοδος ανάλυσης καθυστερήσεων